Social isolation and mental well-being among Korean older adults: a focus on living arrangements - Lee, Geon; Kim, Chulwoo (Frontiers in Public Health, 2024)
Introduction The aging population in South Korea, characterized by an increasing number of older adults living alone, has raised concerns about its implications on mental health, specifically social isolation and loneliness that accompanies solitary living arrangements. This study explores the impact of living arrangements on the mental well-being of Korean older adults by focusing on the prevalence of depression and the role of social isolation in the context of evolving family structures and the COVID-19 pandemic. Methods This cross-sectional study analyzed the responses of older adults aged 65 years and above (mean: 73.1, SD: 5.1) by using data from the Korea National Health and Nutrition Examination Survey conducted in 2018 and 2020. In total, responses from 3,365 older adults (1,653 in 2018 and 1,712 in 2020) were employed in this research. The participants’ mental health status was assessed using the Patient Health Questionnaire-9, with living arrangements categorized by household size. A zero-inflated Poisson regression analysis was employed to investigate the relationship between living arrangements and depression severity, controlling for demographic, socioeconomic, and psychological factors. Results The study found that older adults living with others exhibited a lower depression severity than those living alone. Notably, the severity of depression decreased as the number of household members increased up to a certain threshold. Socio-economic factors, such as income level, marital status, and psychological stress were also identified as significant predictors of depression severity. However, the COVID-19 pandemic did not have a statistically significant impact on depression rates among older adults during the study period. Conclusion Living arrangements play a critical role in the mental health of Korean older adults, with solitary living being associated with higher levels of depression. These findings underscore the importance of social support systems and suggest the need for policies and interventions that promote social connectivity and address the challenges of loneliness faced by them. Future research should explore longitudinal and qualitative studies to further understand causal relationships and develop targeted interventions to improve the mental well-being of the aging population.